2020
DOI: 10.1038/s41418-020-0584-2
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of Ryanodine Receptor 2 impairs neuronal activity-dependent remodeling of dendritic spines and triggers compensatory neuronal hyperexcitability

Abstract: Dendritic spines are postsynaptic domains that shape structural and functional properties of neurons. Upon neuronal activity, Ca 2+ transients trigger signaling cascades that determine the plastic remodeling of dendritic spines, which modulate learning and memory. Here, we study in mice the role of the intracellular Ca 2+ channel Ryanodine Receptor 2 (RyR2) in synaptic plasticity and memory formation. We demonstrate that loss of RyR2 in pyramidal neurons of the hippocampus impairs maintenance and activity-evok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 88 publications
0
21
0
1
Order By: Relevance
“…Recent reports have highlighted the pivotal role of RyR2-mediated Ca 2+ release in dendritic spine remodeling and hippocampal-dependent memory processes (34). Both in vitro and in vivo experiments have confirmed the central role RyR2 channels play in the maintenance and remodeling of dendritic spines, since their loss results in compensatory increases in neuronal excitability and hyperactivity (35). Moreover, neuronal RyR2 channels interact with the L-type Cav1.3 channels; this structural and functional cluster was proposed to have a role in translating synaptic activity into gene expression changes (51).…”
Section: Neurosciencementioning
confidence: 84%
See 1 more Smart Citation
“…Recent reports have highlighted the pivotal role of RyR2-mediated Ca 2+ release in dendritic spine remodeling and hippocampal-dependent memory processes (34). Both in vitro and in vivo experiments have confirmed the central role RyR2 channels play in the maintenance and remodeling of dendritic spines, since their loss results in compensatory increases in neuronal excitability and hyperactivity (35). Moreover, neuronal RyR2 channels interact with the L-type Cav1.3 channels; this structural and functional cluster was proposed to have a role in translating synaptic activity into gene expression changes (51).…”
Section: Neurosciencementioning
confidence: 84%
“…The contribution of RyR2 channels to nuclear Ca 2+ signal generation has not been reported, even though the RyR2 isoform plays key roles in hippocampal structural plasticity and spatial memory processes (34). Moreover, RyR2 loss impairs neuronal activity-dependent remodeling of dendritic spines and triggers compensatory neuronal hyperexcitability (35). We have reported previously that the RyR2 protein content is higher than that of RyR3 and IP 3 R1 both in rat hippocampal primary cultures and in the whole rat hippocampus (36).…”
Section: Significancementioning
confidence: 99%
“…Indeed, it has recently been shown that the loss of RyR2 in the hippocampal pyramidal neurons impaired the maintenance of dendritic spines and activity‐evoked spine plasticity. Furthermore, postdevelopmental deletion of RyR2 resulted in the loss of excitatory synapses, network hyperactivity, and disruption of spatially tuned place cells (Bertan et al., 2020). Moreover, RyR2 downregulation via antisense oligodeoxynucleotides abolished brain‐derived neurotrophic factor (BDNF)‐induced dendritic spine remodeling in cultured hippocampal neurons and severely affected spatial memory (More et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic sparsification, loss of excitatory synapses and over compensatory excitability were also observed. These alterations suggest a crucial role of RyR2 in neurodegenerative diseases [ 93 ].…”
Section: Ryanopathies As a Multiple-organ Dysfunction Syndromementioning
confidence: 99%